Determination of LCt50s in anesthetized rats exposed to aerosolized nerve agents. (February 2013) - Collins, Jennifer L.; Peng, Xinqi; Lee, Robyn; Witriol, Alicia; Pierre, Zdenka; Sciuto, Alfred M.
<x xml:space="preserve">Abstract</x> Nerve agents pose a threat to the respiratory tract with exposure that could result in acute compromised lung performance and death. The determination of toxicity by inhalation is important for the rational development of timely therapeutic countermeasures. This study was designed to deliver aerosolized dilute nerve agents in a dose-response manner to investigate the extent of lethality of nerve agents: soman, sarin, VX and VR. Male rats (240–270 g) were anesthetized intramuscularly with 10 mg/kg xylazine and 90 mg/kg ketamine. Following anesthesia, rats were intubated with a glass endotracheal tube (ET) and placed in a glove box. The ET was connected to a closed circuit nebulizer system (Aeroneb, Aerogen, Inc.) that delivered a particle size of < 2.0 µm and was in series between the ventilator and the ET. Nerve agents were delivered by a small animal ventilator set for a volume of 2.5 mL × 60–80 breaths/min. VX or VR were nebulized and delivered in concentrations ranging from 6.25–800 µg/kg over a 10-min exposure time period. Sarin (GB) or soman (GD), 6.5–1250 µg/kg, were delivered in a similar manner. Lethality by inhalation occurred either during the 10-min exposure period or less than 15 min after the cessation of exposure. Survivors were euthanized at 24 h postexposure. LCt50 estimates (± 95% confidence intervals [CIs]) were obtained from the sequential stage-wise experiments using the probit analysis. Probit analysis revealed that the LD50 for VX was 110.7 µg/kg (CI: 73.5–166.7), VR 64.2 µg/kg (CI: 42.1–97.8); soman (GD), 167 µg/kg (CI: 90–310), and sarin (GB), 154 µg/kg (CI: 98–242), respectively. Although VR is a structural isomer of VX, the compounds appear to be markedly different in terms of toxicity when delivered by aerosol. These relationships were converted to actual 10 min LCt50 equivalents: VX = 632.2, VR = 367, GD = 954.3 and GB = 880 mg·min/m3. Validation of exposure was verified by the determination of blood levels of acetylcholinesterase (AChE) across doses for the agent VR.